2014
DOI: 10.1101/cshperspect.a016147
|View full text |Cite
|
Sign up to set email alerts
|

The Eukaryotic Tree of Life from a Global Phylogenomic Perspective

Abstract: Molecular phylogenetics has revolutionized our knowledge of the eukaryotic tree of life. With the advent of genomics, a new discipline of phylogenetics has emerged: phylogenomics. This method uses large alignments of tens to hundreds of genes to reconstruct evolutionary histories. This approach has led to the resolution of ancient and contentious relationships, notably between the building blocks of the tree (the supergroups), and allowed to place in the tree enigmatic yet important protist lineages for unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
267
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 297 publications
(270 citation statements)
references
References 179 publications
(182 reference statements)
3
267
0
Order By: Relevance
“…To put the 50,118,536 soil protist reads into a phylogenetic context, they were dereplicated into 10,567,804 strictly identical amplicons and placed onto a comprehensive eukaryotic reference tree. The corresponding multiple sequence alignment used to build this tree contained 512 full-length sequences from all major eukaryotic clades (see Supplementary Data 1 and 2 for GenBank accession numbers, sequences and clade assignments), based on the taxon sampling as summarized in a range of pan-eukaryotic phylogenomic studies reviewed in refs 61,62 , with a bias towards lineages known to occur in soils from environmental sequencing studies; for example, refs 35,37,38 . To reduce phylogenetic artefacts, only high quality, full-or near-full length 18S rRNA reads were selected, and reads that have previously been observed to form long branches were omitted.…”
Section: Stampa Plotsmentioning
confidence: 99%
“…To put the 50,118,536 soil protist reads into a phylogenetic context, they were dereplicated into 10,567,804 strictly identical amplicons and placed onto a comprehensive eukaryotic reference tree. The corresponding multiple sequence alignment used to build this tree contained 512 full-length sequences from all major eukaryotic clades (see Supplementary Data 1 and 2 for GenBank accession numbers, sequences and clade assignments), based on the taxon sampling as summarized in a range of pan-eukaryotic phylogenomic studies reviewed in refs 61,62 , with a bias towards lineages known to occur in soils from environmental sequencing studies; for example, refs 35,37,38 . To reduce phylogenetic artefacts, only high quality, full-or near-full length 18S rRNA reads were selected, and reads that have previously been observed to form long branches were omitted.…”
Section: Stampa Plotsmentioning
confidence: 99%
“…Whereas phylogenomic analyses robustly recover the monophyly of Opisthokonta, Amoebozoa and SAR, the phylogenetic coherence of Excavata, Archaeplastida, and Hacrobia is less certain (see also Fig. 1) (Burki et al 2008Hampl et al 2009;Parfrey et al 2010;Brown et al 2012;Zhao et al 2012;Burki 2014).…”
Section: The Eukaryotic Tree Of Lifementioning
confidence: 99%
“…The most recent conceptions of the eukaryotic tree of life feature five or six "supergroups" (Keeling et al 2005;Roger and Simpson 2009;Burki 2014) including Opisthokonta, Amoebozoa, Excavata, the SAR group, Archaeplastida, and Hacrobia (Haptophyta and Cryptophyta). Whereas phylogenomic analyses robustly recover the monophyly of Opisthokonta, Amoebozoa and SAR, the phylogenetic coherence of Excavata, Archaeplastida, and Hacrobia is less certain (see also Fig.…”
Section: The Eukaryotic Tree Of Lifementioning
confidence: 99%
“…It was suggested that the root of the eukaryote phylogeny lies between Opisthokonta plus Amoebozoa on one side and the remaining supergroups on the other, with the clades on either side denoted unikonts and bikonts (114,115). This scheme was adopted by the scientific community and taken for granted, even though improvements in phylogenetic methods and new genome-scale data from an ever-growing number of phylogenetically diverse lineages led to substantial modifications (2,112). First, Chromalveolata is nonmonophyletic and has been superseded by a robustly supported grouping dubbed SAR, which integrates Rhizaria (demoted from supergroup status), but leaves out some chromalveolate lineages (haptophytes and cryptophytes) (2,116,117).…”
Section: Further Considerations and Conclusionmentioning
confidence: 99%
“…2. We focus only on the most salient aspects and latest updates; interested readers may consult excellent recent reviews (112). A decade-old scheme based on molecular phylogenetic evidence, cytological features, and limited comparative genomic data divides nearly all extant eukaryotes into six major presumably monophyletic assemblages, so-called supergroups: Opisthokonta, Amoebozoa, Excavata, Archaeplastida, Chromalveolata, and Rhizaria (113).…”
Section: Further Considerations and Conclusionmentioning
confidence: 99%